Filmwise condensation of steam on vertical plates with novel pin fin arrays produced by selective laser melting - Ho, Jin Yao (2019)
An experimental investigation of the use of pin fin arrays to enhance filmwise condensation of steam on vertical plates was carried out. New fin geometries of cylindrical, conical and sinusoidal profiles were produced and investigated in a condensation chamber. The effects of fin geometry and fin height were systematically examined and a comparison of the heat transfer performances of the pin fin structures and equivalent longitudinal fins was made. Visualization studies were carried to determine the condensate retention heights of the various fin structures and to elucidate the possible mechanisms affecting the condensation heat transfer coefficient. Our results show that the pin fin structures exhibit higher heat transfer performances as compared to the equivalent longitudinal fins of the same fin base diameter/width, pitch and height even though the longitudinal fins have larger heat transfer area as compared to the pin fins. The conical fin geometry of Specimen C1 was shown to promote condensate drainage away from the specimen surface, which reduced the condensate retention height and enhanced the heat transfer. In addition, the three-dimensional geometry of the conical fin also resulted in additional variation of curvature that reduces the film thickness near the fin tip and promotes heat transfer. On the other hand, the sinusoidal fin geometry of Specimen S1 promoted the draining of the condensate film from the fin tip to the fin base which significantly improved heat transfer near the fin tip. In comparison with the plain surface, enhancement factors (η) of 2.04 and 1.80 were achieved with Specimens C1 and S1, respectively.